Development of a Web Application for Historical Building Management through BIM Technology - Rodrigues, Hugo; Matos, R.; Teixeira, J.; Rodrigues, F. (Advances in civil engineering, 2019)
Nowadays the built heritage has been recognized as one of the main sectors that can support the economic and sustainable development of countries. In the last years, the built heritage has been subject to several levels of interventions, being now clear its need for a proper maintenance and conservation management. However, in several cases, the maintenance faces lack of building records, which makes the maintenance a harsh, long, and expensive process. Therefore, there is an opportunity and need to apply new technologies, like Building Information Modelling (BIM), as supporting tool to the management of historical heritage. By so, the aim of this work was the development of a management system to be used as a supporting tool to the maintenance and conservation of the existent buildings, in historical context, facilitating to the interested parties the automated and digitized information needed to carry out the most varied tasks, with the particularity to be directly connected to the 3D-BIM model of the building. But in order to test the developed system (its applicability and functionality), it was in an early phase, applied to a pilot project with the significant heritage value. This work follows a development methodology applied to the case study and had different phases: (1) the case study was modelled in Autodesk Revit software, in whose model was inserted all the parametric information and associated metadata; (2) then, a support database of the management system was developed in Microsoft SQL Server, which will support all the information exported from the BIM model; (3) a web application was developed in C# through Visual Studio 2015, which works through and application programming interface (API) allowing the communication between the web application and the BIM model, allowing not only the interaction with the parametric information of this one, but also, a persistent access to a data management system (drawings, inspection reports, specifications, etc.) that has been created. The development of the management system and its application to the case study allows us to show its potential as a tool for the historical heritage management, contributing to its permanent and constantly updated management and cross off the fragmentation and loss of information therefore reducing the consequent investment in data collection.